A career in corrections guided by these core beliefs. - Wilkinson, Reginald A. (Corrections Today)
The article reflects on a lifelong career in corrections, emphasizing that the work is driven by core beliefs centered on continuous improvement, valuing people, and pursuing excellence. Topics include leadership development, the importance of respect and compassion, and the personal commitment required to foster progress in the corrections field.